Analysis Of The Determinants Of Labor Productivity In Dompu District NTB Province - Arifin Arifin; M. Irwan M. Irwan; Subhan Purwadinata (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the determinants of labor productivity in Dompu Regency, West Nusa Tenggara Province. The study employed a quantitative approach with an associative research design. The data used were secondary time-series data covering the period 1993–2025, obtained from Statistics Indonesia (BPS) and other official publications. Data were analyzed using multiple linear regression with the assistance of SPSS, preceded by classical assumption tests. The results indicate that the Human Development Index, Minimum Wage, and Economic Growth each have a positive and statistically significant effect on labor productivity. Simultaneously, these three independent variables also have a significant effect on labor productivity in Dompu Regency. These findings suggest that improving human resource quality, implementing adequate wage policies, and promoting sustainable economic growth play important roles in enhancing labor productivity. Therefore, these aspects should be prioritized in the formulation of regional development policies.